The Impact of Climate-Induced Resource Conflicts on Arms Proliferation - Jamiu, Mubarak; Febriansyah, Muhammad (Journal of Techno-Social, 2026)
This study explores the complex interplay between climate change, resource scarcity, and the proliferation of small arms and light weapons (SALWs) in Northwestern Nigeria, a region deeply affected by environmental stressors. As climate change exacerbates desertification, irregular rainfall, and shrinking agricultural viability, competition for vital resources such as land and water has intensified, leading to violent conflicts, particularly between farmers and pastoralists. These conflicts, driven by climate-induced stressors and socio-economic inequalities, have escalated the need for small arms, which are increasingly used for self-defense, territorial assertion, and survival. Drawing on Ecological Theory and Conflict Resolution Theory, this research identifies the key factors driving SALWs proliferation, including poor border security, local arms manufacturing, political marginalization, and unemployment. The study demonstrates how the porosity of borders and the weakness of security forces facilitate the illicit flow of weapons, while socio-political factors, such as ethnic divisions and political thuggery, further exacerbate the proliferation of small arms. Through a detailed analysis of these drivers, the study underscores the urgent need for comprehensive strategies that address both the environmental and socio-political roots of conflict. The findings emphasize the importance of strengthening border security, implementing climate-resilient resource management, and promoting inclusive conflict resolution mechanisms at the local level. Recommendations also call for a concerted effort to tackle poverty, unemployment, and marginalization, while enhancing regional cooperation and governance reforms to reduce the proliferation of SALWs and promote long-term peace and stability in climate-affected conflict zones. This research contributes to the growing body of literature on climate change, armed violence, and national security, offering valuable insights for policymakers and security experts seeking to address the multifaceted challenges of small arms proliferation in the context of climate-induced resource conflicts.